Programma: 24 december Super's Ragga Experience; 26 december The Soft Parade; 28 december Van Dik Hout; 29 december Dj's on a mission; 30 december Tatunane
Programma: 24 december Super's Ragga Experience; 26 december The Soft Parade; 28 december Van Dik Hout; 29 december Dj's on a mission; 30 december Tatunane.